Sylloge nummorum Graecorum [Great Britain], vol. XII : The Hunterian Museum University of Glasgow, part 2 : Roman provincial coins Cyprus-Egypt. - Goddard, John. (Oxford ; New York)
s. [15], clxxiv-cccxxxii, [158], [42]